2015
DOI: 10.1177/1477153515574222
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the harshness–softness attribute of shadows

Abstract: A shadow has two different attributes, harshness-softness and lightnessdarkness. A three-phase study designed to quantify these shadow characteristics has been carried out. In the first phase, numerous computer-generated examples of shadows were produced and their harshness-softness attribute was evaluated. The harshness-softness of shadows was graded based on the visual evaluation performed in this phase. In the second phase, the lightness-darkness attribute was graded depending on a calculation-based approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Painters executed their art at the same time of day and under the same lighting conditions to preserve the visual mark of the painting. Shadows change with lighting conditions, becoming darker, lighter, sharper, softer, longer, shorter, which affects the viewer's attitude towards it [43]. A shadow can be looked at, or looked through, depending on the differences in the perception of the brightness constancy of a painting.…”
Section: The Role Of Shadowmentioning
confidence: 99%
“…Painters executed their art at the same time of day and under the same lighting conditions to preserve the visual mark of the painting. Shadows change with lighting conditions, becoming darker, lighter, sharper, softer, longer, shorter, which affects the viewer's attitude towards it [43]. A shadow can be looked at, or looked through, depending on the differences in the perception of the brightness constancy of a painting.…”
Section: The Role Of Shadowmentioning
confidence: 99%
“…33 Yag˘mur and Ozturk recently found that the harshness-softness attribute of castshadows also depends on the scale of light; the shadows are softer when the luminaire size increases, or the object size decreases. 36 Frandsen's approach is analogous to our 'probe in a sphere' approach. In Frandsen's theory, the solid angle of light source ( in our model) varied from narrow (i.e.…”
Section: Theorymentioning
confidence: 99%
“…33 Yağmur and Ozturk recently found that the harshness-softness attribute of cast-shadows also depends on the scale of light; the shadows are softer when the luminaire size increases, or the object size decreases. 36…”
Section: Frandsen’s Scale Of Lightmentioning
confidence: 99%